Bali: Tourism Economy The End Of 2021, Will Fly High Again? - I Nyoman Sudapet; Ronny Durrotun Nasihien; Muhammad Ikhsan Setiawan; Agus Sukoco; Elok Damayanti; Amrun Rosyid; Che Zalina Zulkifli; Abdul Talib Bon (LPPM of NAROTAMA UNIVERSITY, 2021)
Based on the Bali Economic Quarterly Development document for the second quarter of 2021 by BPS, from the beginning of 2020 until now, the Covid-19 pandemic has continued to infect Indonesia. Even the number of new cases affected by this disease is increasing. Based on data from the Covid-19 Handling Task Force, as of June 30, 2021, the number of daily new confirmed cases reached around 21,000. Not only attacking the health sector, but this pandemic has also shattered the joints of the economy. Various government efforts carried out in 2021 have been able to withstand the economic contraction year on year. In the second quarter of 2021, Indonesia's economic growth year on year was recorded at 7.07 percent and was the first positive growth since the second quarter of 2020. In particular, the tourism sector became the sector that experienced the highest growth in the second quarter of 2021. The transportation and accommodation provision business fields, which are the business fields most closely related to the tourism sector, are the two categories that experienced the highest growth, namely by 25.10 percent and 21.58 percent. Among all provinces in Indonesia, Bali can be said to be one of the provinces most affected by the Covid-19 pandemic. Bali's dependence on foreign tourist visits has caused Bali to still slump in the economy. Since March 2020, the arrival of foreign tourists to Bali has continued to decline. The decline even reached almost 100 percent when compared to the same months the previous year.